![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
展开全部
e^2y-xy+2=0
2e^2y*y' - y - xy' = 0
(2e^2y - x)y' = y
y' = y/(2e^2y - x)
y" = (y/(2e^2y - x))'
=(y'(2e^2y-x)-y(2e^2y-x)')/(2e^2y-x)^2
=(y'(2e^2y-x)-y(4e^2y*y'-1))/(2e^2y-x)^2
=(y-y(4e^2y*y/(2e^2y - x)-1))/(2e^2y-x)^2
2e^2y*y' - y - xy' = 0
(2e^2y - x)y' = y
y' = y/(2e^2y - x)
y" = (y/(2e^2y - x))'
=(y'(2e^2y-x)-y(2e^2y-x)')/(2e^2y-x)^2
=(y'(2e^2y-x)-y(4e^2y*y'-1))/(2e^2y-x)^2
=(y-y(4e^2y*y/(2e^2y - x)-1))/(2e^2y-x)^2
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询